A Cluster Randomized Controlled Trial of the Archena Infancia Saludable Project on 24-h Movement Behaviors and Adherence to the Mediterranean Diet among Schoolchildren: A Pilot Study Protocol - José Francisco López-Gil; Antonio García-Hermoso; Lee Smith; Alejandra Gallego; Desirée Victoria-Montesinos; Yasmin Ezzatvar; Maria S. Hershey; Héctor Gutiérrez-Espinoza; Arthur Eumann Mesas; Estela Jiménez-López; Pedro Antonio Sánchez-Miguel; Alba López-Benavente; et al. (MDPI AG, 2023)
Objective: The aim of this paper is to describe the protocol of pilot cluster randomized controlled trial (RCT) that will evaluate the effects of a lifestyle-based intervention. The Archena Infancia Saludable project will have several objectives. The primary objective of this project is to determine the 6-month effects of a lifestyle-based intervention on adherence to 24-h movement behaviors and Mediterranean diet (MedDiet) in schoolchildren. The secondary objective of this project is to test the intervention effects of this lifestyle-based intervention on a relevant set of health-related outcomes (i.e., anthropometric measurements, blood pressure, perceived physical fitness, sleep habits, and academic performance). The tertiary objective is to investigate this intervention's "halo" effect on parents'/guardians' 24-h movement behaviors and adherence to the MedDiet. Methods: The Archena Infancia Saludable trial will be a cluster RCT submitted to the Clinical Trials Registry. The protocol will be developed according to SPIRIT guidelines for RCTs and CONSORT statement extension for cluster RCTs. A total of 153 eligible parents/guardians with schoolchildren aged 6-13 years will be randomized into an intervention group or a control group. This project focuses on two fundamental pillars: 24-h movement behaviors and MedDiet. It will mainly focus on the relationship between parents/guardians and their children. Behavior change strategies for dietary and 24-h movement behaviors in schoolchildren will be based on healthy lifestyle education for parents/guardians through infographics, video recipes, brief video clips, and videos. Conclusions: Most of the current knowledge on 24-h movement behaviors and adherence to the MedDiet is based on cross-sectional or longitudinal cohort studies, warranting a need to design and conduct RCTs to obtain more robust evidence on the effect of a healthy lifestyle program to increase 24-h movement behaviors and to improve adherence to the MedDiet in schoolchildren.